Children’s Religious Coping Scale: Adaptation and Psychometric Properties - Strelhow, Miriam Raquel Wachholz; Bedin, Livia Maria; Sarriera, Jorge Castellá (Paidéia (Ribeirão Preto), 2017)
Religious coping refers to the use of strategies related to religious faith in coping with stressful situations. This study presents the adaptation of the Children's Religious Coping scale (CRC) for Brazilian children and verifies its psychometric properties. Participants are 1,612 children (54.71% girls) between 8 and 13 years old (M = 10.19, SD = 1.47). Principal component and confirmatory factor analyses indicated that the CRC was composed of two dimensions: Positive Religious Coping, with 17 items in three factors (Belief in God's support, Seeking the religious institution, Intercession), and Negative Religious Coping, consisting of 11 items in three factors (Dissatisfaction with God or others, Negative reappraisal of meaning, Punishing reappraisal). The instrument showed adequate reliability, multigroup confirmatory factor analyses indicated that the items factor weights are similar by sex. The scale showed good fit indices for this sample, demonstrating that it can be a promising instrument for future research.